Techno-economic design and performance analysis of nanogrid systems for households in energy-poor villages. (October 2017) - Akinyele, Daniel
Highlights: A 5–14.5 kW solar nanogrid has been modeled for demand of 12.5–36.5 kWh/d. The yield and losses of the solar nanogrid are 4.22 and 1.23 h/d, respectively. The yearly availability of 100% is achieved by hybrid nanogrid systems. The hybrid nanogrid systems provide better battery energy profiles than the solar nanogrid system. The lifecycle costs of the diesel nanogrid is 1.62–2.15 times the values obtained for renewable energy nanogrids. Abstract: This paper presents the techno-economic design and analysis of a nanogrid system for five neighboring houses, using an energy-poor village in Gwagwalada-Abuja, Nigeria as a case study. It explores the possibility of different energy configurations – solar nanogrid (SNg), solar/wind nanogrid (SWNg), solar/diesel nanogrid (SDNg), solar/wind/diesel nanogrid (SWDNg) and diesel nanogrid (DNg) systems. The study uses the demand patterns obtained during a field survey to determine the aggregate load profile and the energy generation systems. It presents detailed capacities, annual energy, losses, battery state of charge (SoC), unmet demand, loss of load probability (LOLP), availability and the demand growth analyses. Results reveal that 5–14.5 kW SNg can meet the users' demand of ∼ 12.5–36.5 kWh/d achieving an availability of 99.2–99.6%. However, an availability of 100% was obtained for the hybrid options, including the DNg. These are 2.5–7 kW PV and a 1.8–3.6 kW wind generator; 5 kW PV and 5 kW diesel systems; 2.5 PV, 1.8 kW wind and 5 kW diesel system; 2.5–5 kW diesel generator systems. The results also demonstrate that the hybrid nanogrids achieves better battery profiles compared to the single-source option because of their complementary characteristics; thus, satisfying the battery constraint of SoC ≥ 30% during the year. The initial cost of the DNg option is ∼6–22% of those of the renewable energy-based nanogrids. The study further reveals that nanogrids with diesel generators have relatively higher life cycle costs because of the fuel costs. Though renewable energy-based nanogrids have relatively higher initial capital costs, their life cycle costs are lower than those of the DNg. The research can be used for planning new electrification systems for rural communities around the globe.